Comparative parasitological and electron microscopic studies on the effects of Nitazoxanide and Praziquantel in Schistosoma mansoni-infected mice - A. El-Taweel, Hend; H. El-Sayad, Mona; A. Abu Helw, Sahar; A. Al-Kazzaz, Mohammad (International Journal of Pharmacology and Toxicology, 2016)
This study was designed to evaluate antischistosomal activity of Nitazoxanide (NTZ) in Schistosoma mansoni-infected mice compared to Praziquantel (PZQ). Fifty four infected mice were recruited into 3 groups, each of 18 mice. Group 1 was infected non-treated control. Group 2 was infected and then treated with PZQ 500 mg for two days, and group 3 was infected and treated with NTZ 100 mg/kg for seven days. Efficacy of drugs was assessed by Parasitological, and scanning electron microscopic studies. PZQ reduced (4.9%, 22.5% and 50.7%) of faecal eggs, (22%, 22.6% and 55.1%) of intestinal eggs, (20.4%, 44.3% and 46.7%) of hepatic egg counts and (27%, 45.1% and 64.9%) of total worm load whereas, NTZ reduced (4.9%, 22.5% and 50.7%),of faecal eggs, (22%, 22.6% and 55.1%) of intestinal eggs ,(20.4%, 44.3% and 46.7%) of hepatic egg counts and (27%, 45.1% and 64.9%) of total worm load at 1, 2 and 4 WPT, respectively. The percentages of dead eggs were more than 80% after PZQ treatment and only 30% after NTZ at 4 WPT. PZQ showed extensive tegumental damages in male and female worms more than NTZ at 2 WPT. Our findings concluded that Nitazoxanide showed weaker antischistosomal activity in animal models than praziquantel.